Gamification on Sales Force Performance in Nigeria Bottling Company - S. A, Yusuff; M. S, Oladimeji; O. L, Ahmodu; A. B, Adeniyi (Games Review, 2019)
This study empirically examined gamification as a new approach of getting performance from sales employees. It examined a sales man from the perspective of game player, thereby applying those factors that motivate a player to win a game such as points, the rewards, and achievement levels to get performance from salesmen. The sales performance we examined includes; customer, conversion ratio, referral rate, cancellation recovery rate and organizational profitability. The study was conducted on sales personnel of Nigeria Bottling Company Ltd South-West Region. The population of the study was 210 professional sales personnel of the company with the sample size of 138 using the Taro Yamane formula to determine the sample size. The simple random sampling technique was used to select the respondents. A structured questionnaire was used to elicit information from the respondents. The data collected were analyzed through test-re-test method. A pilot study was adopted to test the reliability of the instrument. Analysis of data was done through the use of SPSS. The study employed descriptive and Pearson Product Moment Correlation (PPMC) type of inferential statistics to test the hypotheses. The study showed that earn point by salesman has positive impact on sales force performance. Also, sales achievement levels have significant impact on organizational performance. Based on these findings, the study therefore recommends that Nigeria Bottling Company should continue to use earn point and sales achievement levels as proxy to gamification which enhances sales performance, thereby improving the performance of the organization.